Plasma-enhanced direct conversion of CO2 to CO over oxygen-deficient Mo-doped CeO2. Issue 94 (13th November 2020) - Wang, Li; Du, Xiaomin; Yi, Yanhui; Wang, Hongyang; Gul, Masaud; Zhu, Yimin; Tu, Xin
Abstract : Oxygen-deficient Mo-doped CeO2 showed significantly higher CO2 conversion compared to pure CeO2 in the plasma splitting of CO2 . Abstract : Plasma CO2 splitting to CO over oxygen-deficient Mo-doped CeO2 under mild conditions was investigated for the first time, showing ∼20 times higher CO2 conversion compared to pure CeO2, which can be attributed to the increased oxygen vacancies (VO ) and the formation of Ce 3+ –VO –Mo on the catalyst surface. Importantly, VO sites showed excellent catalytic stability.